Increase in Middle East Respiratory Syndrome-Coronavirus Cases in Saudi Arabia Linked to Hospital Outbreak With Continued Circulation of Recombinant Virus, July 1–August 31, 2015. (3rd August 2016) - Assiri, Abdullah M.; Biggs, Holly M.; Abedi, Glen R.; Lu, Xiaoyan; Bin Saeed, Abdulaziz; Abdalla, Osman; Mohammed, Mutaz; Al-Abdely, Hail M.; Algarni, Homoud S.; Alhakeem, Raafat F.; Almasri, Malak M.; Alsharef, Ali A.; et al.
Abstract: During July–August 2015, the number of cases of Middle East respiratory syndrome (MERS) reported from Saudi Arabia increased dramatically. We reviewed the 143 confirmed cases from this period and classified each based upon likely transmission source. We found that the surge in cases resulted predominantly (90%) from secondary transmission largely attributable to an outbreak at a single healthcare facility in Riyadh. Genome sequencing of MERS coronavirus from 6 cases demonstrated continued circulation of the recently described recombinant virus. A single unique frameshift deletion in open reading frame 5 was detected in the viral sequence from 1 case.